2008
DOI: 10.1007/s12291-008-0015-5
|View full text |Cite
|
Sign up to set email alerts
|

Protective influence of vitamin E on the antioxidant defence system in the whole blood and liver of normal and alloxan-induced diabetic rats

Abstract: The effect of oral administration of vitamin E for twenty-eight consecutive days on blood glucose, reduced glutathione levels, antioxidant enzymes (superoxide dismutase and catalase activities), and levels of malondialdehyde (as an index of free radical-mediated lipid peroxidation) was observed in the whole blood and liver of normal and alloxan-induced diabetic rats. It was found that oral administration of vitamin E significantly (p<0.05) lowered the blood glucose level and increased the body weight of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
2
0
0
Order By: Relevance
“…In liver homogenates of preventively AAEO treated broilers and then infected (group D 2 ) was observed a significant increase of GSH content, decrease of LPx content, induction of GSHPx activity and inhibition of POD, SOD, GR and XOD activity in comparison with the control group A. This finding is in line with data published by Olanlokun (2008). Observed changes show positive preventive effects of applied AAEO.…”
Section: Enzymatic Activity In Liver Homogenatessupporting
confidence: 90%
“…In liver homogenates of preventively AAEO treated broilers and then infected (group D 2 ) was observed a significant increase of GSH content, decrease of LPx content, induction of GSHPx activity and inhibition of POD, SOD, GR and XOD activity in comparison with the control group A. This finding is in line with data published by Olanlokun (2008). Observed changes show positive preventive effects of applied AAEO.…”
Section: Enzymatic Activity In Liver Homogenatessupporting
confidence: 90%
“…hence, SINGh et al (2011) reported that an increase in catalytic activity of superoxide-dismutase is expected as part of the system defense. KOSTADINOVIĆ et al (2015) showed that addition of Artemisa absinthium to broiler diet led to higher SOD activity in hemolysed blood and liver homogenates, which was also in agreement with the results reported by OLANLOKUN (2008). On the other hand, KOSTADINOVIĆ et al (2015) reported that GShPx levels were not altered by Artemisia absinthium supplementation, which is not in accordance with the results obtained in this study.…”
Section: Discussionsupporting
confidence: 75%